The Implementation of Cognitive and Constructivism Theory in Media Activities for Sakubun in Seventh Semester at Bina Nusantara University - Nalti Novianti (Bina Nusantara University, 2012)
Sakubun is a combination of courses between the language and writing skills. Normally, Japanese language teachers regard this course as hard and difficult. Besides examining the grammar, the teacher has to think really hard to guess the real meaning of the sentences or expressions that the students want to say. Therefore, in order to simplify the process of checking and grading, the writer has conducted a small research toward a Sakubun class. This research was directed to the 7th semester Sakubun class using the Cognitive and the Constructivism theory. Those theories were implemented in four different media as part of the class course material. By differentiating teaching media, learners will not easily become bored during learning process. Teachers could also easily divide the type of materials into two namely: visual and the non-visual, which made learners could easily develop their creativity based on their own personal preferences. The result of the research has shown that there was an improvement of skill in the small group in applying the grammar. This research was conducted during the short semester starting in June until August 2011.